2009
DOI: 10.1177/1076029609350890
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-Activatable Fibrinolysis Inhibitor (TAFI) Antigen and Activity Assay in Patients With Primary Hypothyroidism

Abstract: Hypothyroidism causes a tendency for cardiovascular diseases. It was recently shown that thrombin-activatable fibrinolysis inhibitor (TAFI) attenuates fibrinolysis and also fibrin-plasminogen interaction by the removal of lysine and arginine residues from fibrin monomers. The aim of this study was to determine the effects of overt hypothyroidism on the levels of TAFI antigen (TAFI Ag) and TAFI activity (TAFIa). Thirty-one overt primary hypothyroid patients and age- and gender-matched 25 healthy controls were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…This process results in less plasmin formation. TAFI attenuates the fibrinolytic system by inhibiting the binding of plasminogen to fibrin and attenuation of fibrin-plasminogen interaction that causes inhibition of fibrinolysis and a tendency to thrombosis ( 59 - 62 ). The elevation of TAFI antigen is a cause of hypofibrinolysis in several endocrinological disorders ( 63 , 64 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process results in less plasmin formation. TAFI attenuates the fibrinolytic system by inhibiting the binding of plasminogen to fibrin and attenuation of fibrin-plasminogen interaction that causes inhibition of fibrinolysis and a tendency to thrombosis ( 59 - 62 ). The elevation of TAFI antigen is a cause of hypofibrinolysis in several endocrinological disorders ( 63 , 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…PAI-1 and t-pA, however, were similar between two groups. The authors believe that fibrinolytic activity substantially decreases when hypothyroidism gets more severe and thyroid hormone therapy to restore euthyroidism may be important in ameliorating the increased risk of cardiovascular events ( 62 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, inadequate thyroid hormone has widespread consequences for the body. Some studies have shown that hypothyroidism may induce delayed skeletal development [3], cardiovascular diseases [4], secondary hypertension [5], deterioration of human reproductive health [6], and changes in the brain structure and function [7].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, it was reported that in hypothyroidism the thrombin-activated fibrinolysis inhibitor (TAFI), which attenuates fibrinolysis and lowers fibrin-plasminogen interaction by the removal of lysine-arginine residues from fibrin monomers, and TAFI antigen are increased. 70 These results suggest that fibrinolytic activity is decreased in hypothyroidism. Decreased fibrinolytic activity, expressed by lower D-dimer levels, higher a2 antiplasmin activity, and increased levels of tissue plasminogen activator inhibitor antigen, was reported in patients with progressive moderate to severe hypothyroidism.…”
Section: Subclinical Hypothyroidism and Hemostasismentioning
confidence: 86%